Poetyka – estetyka – metafizyka - Gadamska-Serafin, Renata (Wydawnictwo Uniwersytetu Rzeszowskiego, 2013)
The modern era has developed poetics very different from Plato’s philosophy of objective beauty and generally inconsistent with or at least indifferent to metaphysics (Baumgarten, Kant). Also romanticists, especially those whose theoretical and literary thought followed the German idealism, were often detached from metaphysical ground (in its proper sense). The natural consequence of choosing this particular way of thinking in the modern paradigm in the 20th century has been the postmodern polyphony in literary theory. A separate and a very mature attitude regarding the form of poetics and its theoretical considerations has been adopted by the author of "Rzecz o wolności słowa" ("About the Freedom of the Word"), who referred to the metaphysical category of "mimesis" (closely linked to his concept of man – "imago Dei") and returned to the concept of objective beauty ("Promethidion"), thus radically overcoming the weakness of modern poetics.
Poetics – Aesthtics – Metaphysics
Keywords: poetyka; estetyka; metafizyka; Norwid Cyprian; romantyzm; naśladowanie; kreacja; piękno; prawda